1998
DOI: 10.1111/j.1469-7998.1998.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of burrowing, running, and free‐living in the Namib Desert golden mole (Eremitalpa namibensis)

Abstract: The Namib Desert golden mole (Eremitalpa granti namibensis) is a small (c. 20 g), blind, sand-swimming, chrysochlorid insectivore that inhabits the sand dunes of one of the driest and least productive areas of the world. Its food, largely termites, is sparse and occurs in widely distributed patches, and free water is unavailable. The moles forage by running on the surface and burrowing below the sand. We estimated their daily energy expenditure in the ®eld to be 11.8 kJ d -1 by constructing a`distance-energy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(15 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The unique underground lifestyle of the subterranean rodents determines high energy expenditure in their life history such as digging format, foraging and other activities [ 25 , 26 ]. For foraging, the energy consumption is enormous, so they need to have a more efficient diet digestibility to buffer the energy expenditure [ 27 , 28 ]. Plateau zokor, a typical subterranean rodent, is accompanied by excavation activities and consumes more energy compared with ground rodents [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique underground lifestyle of the subterranean rodents determines high energy expenditure in their life history such as digging format, foraging and other activities [ 25 , 26 ]. For foraging, the energy consumption is enormous, so they need to have a more efficient diet digestibility to buffer the energy expenditure [ 27 , 28 ]. Plateau zokor, a typical subterranean rodent, is accompanied by excavation activities and consumes more energy compared with ground rodents [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plateau zokor ( Eospalax baileyi ) is a solitary and entirely subterranean burrowing endemic rodent species, inhabiting areas of 2600 to 4600 m above sea level on Qinghai-Tibet Plateau [ 23 , 24 ]. Plateau zokor spend most their life in underground nests and foraging, and burrowing activity mainly takes place at a depth of 3–20 cm under the ground [ 28 ]. This underground lifestyle means that plateau zokor must excavate for courtship and foraging [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bergh and Ekblom, 1979;Sawka et al, 2012) are rare, largely because of the difficulties in manipulating T b in a standardisable way. A handful of studies, mostly in small mammals, have been able to measure wholebody performance (in the form of righting time, running speed or the ability to pull a weight) at higher T b with mixed results, with some showing an increase in performance at higher T b (Seymour et al, 1998;Rojas et al, 2012;Stawski et al, 2017;Treat et al, 2018), whereas others found no difference (Wooden and Walsberg, 2004). Studies that directly measure muscle performance in relation to muscle temperature in endotherms (with the exception of studies on humans) are equally rare and have found differences according to which muscle (core versus periphery) is measured, the temperatures under which the muscles developed, as well as the species (Angilletta et al, 2010;James et al, 2015;Little and Seebacher, 2016;Rummel et al, 2018).…”
Section: Defining Performance and Linking It To Body Temperaturementioning
confidence: 99%
“…The raw recordings of CO 2 production were instantaneously corrected by applying an empirically derived washout constant for the chamber using previously described principles (Seymour et al, 1998). Instantaneous CO 2 production rates (µmol s −1 ) were calculated as the product of incurrent flow rate and the fraction of CO 2 added to the excurrent air (Lighton, 2008), and then converted to instantaneous metabolic rate (mW) assuming a respiratory exchange ratio of 0.86, as determined in pilot experiments, and a conversion factor of 0.54 J µmol −1 (Withers, 1992).…”
Section: Flight Respirometrymentioning
confidence: 99%